2010
DOI: 10.1200/jco.2009.26.4556
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab Plus Fludarabine and Cyclophosphamide Prolongs Progression-Free Survival Compared With Fludarabine and Cyclophosphamide Alone in Previously Treated Chronic Lymphocytic Leukemia

Abstract: R-FC significantly improved the outcome of patients with previously treated CLL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
262
4
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 430 publications
(287 citation statements)
references
References 44 publications
13
262
4
4
Order By: Relevance
“…The OR for all patients was 62%. This rate was comparable with that achieved in pretreated patients within the REACH trial with the FCR regimen and with FC plus alemtuzumab (OR: 69.9% and 67%, respectively) [27,28], and higher than that reported for alemtuzumab monotherapy (OR: 34%) [5]. It is noteworthy that the REACH trial did not include fludarabinerefractory patients, and the 17p deletion was present in only 7% of the patients.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The OR for all patients was 62%. This rate was comparable with that achieved in pretreated patients within the REACH trial with the FCR regimen and with FC plus alemtuzumab (OR: 69.9% and 67%, respectively) [27,28], and higher than that reported for alemtuzumab monotherapy (OR: 34%) [5]. It is noteworthy that the REACH trial did not include fludarabinerefractory patients, and the 17p deletion was present in only 7% of the patients.…”
Section: Discussionsupporting
confidence: 72%
“…Nevertheless, neutropenic fever was rare (8%). The majority of patients treated with the FCR regimen [27] for relapsed CLL experienced grade III-IV neutropenia (89%), which was complicated by neutropenic fever in 12% of the patients. Because of the presence of adverse events, approximately 50% of refractory patients treated with fludarabine combination regimens need to have dose reductions, skip courses of treatment, or have delays in administration of therapy because of myelosuppression [30,31], while our patients completed the planned 4 R-BAC cycles in 69% of cases with only 9% of cycles that were delayed.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, Robak et al reported the benefit of chemoimmunotherapy compared to chemotherapy alone in patients with previously treated CLL [9]. The response rates in this trial are consistent with prior phase 2 trials using the identical combination.…”
Section: Commentssupporting
confidence: 76%
“…22,23 Rituximab was added to the DHAP chemotherapy backbone as it appeared to be of additive value in the relapsed setting when combined with chemotherapy. 24,25 …”
Section: Introductionmentioning
confidence: 99%